Biphasic Effect of ATP on In Vitro Mineralization of Dental Pulp Cells. Issue 1 (7th July 2017) - Techatharatip, Oranuch; Nowwarote, Nunthawan; Taebunpakul, Suthisa; Pavasant, Prasit
ABSTRACT: Dental pulp cells release adenosine triphosphate (ATP) in response to intrapulpal pressure and the amount released depends on the magnitude of the pressure. ATP regulates the differentiation of stem cells into adipocytes and osteoblasts. However, it is unknown whether extracellular ATP influences the stemness and osteogenic differentiation of stem cells from human exfoliated deciduous teeth (SHEDs). Therefore, this study investigated the effects of extracellular ATP at a low (0.1 μM) and high (10 μM) concentration on the stemness and osteogenic differentiation of SHEDs. Cells were cultured in either growth medium or osteogenic medium with or without 0.1–10 μM ATP. In growth medium, both concentrations of ATP increased the mRNA expression of pluripotent and osteogenic markers. In contrast, in osteogenic medium, 0.1 μM ATP enhanced in vitro mineralization, whereas 10 μM ATP inhibited this process. In addition, 10 μM ATP stimulated the mRNA expression and activity of ectonucleotide pyrophosphatase/phosphodiesterase (ENPP), an enzyme that regulates the phosphate/pyrophosphate ratio. Thus, depending on the growth condition and its concentration, ATP stimulated stemness and in vitro mineralization or inhibited mineralization. In growth medium, both ATP concentrations stimulated pluripotent and osteogenic marker gene expression. However, in osteogenic medium, a biphasic effect was found on in vitro mineralization; the low concentration stimulated, whereas the high concentration inhibited, mineralization. We propose that ATP released due to mechanical stress modulates the stemness and differentiation of SHEDs. J. Cell. Biochem. 119: 488–498, 2018. © 2017 Wiley Periodicals, Inc. Abstract : The effect of ATP on in vitro mineralization in SHEDs proved to be biphasic; a low concentration had a stimulating whereas a high concentration had an inhibiting effect.